BUDAYA DAN KEBUDAYAAN: TINJAUAN DARI BERBAGAI PAKAR, WUJUD-WUJUD KEBUDAYAAN, 7 UNSUR KEBUDAYAAN YANG BERSIFAT UNIVERSAL - Abdul Wahab Syakhrani; Muhammad Luthfi Kamil (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
It can be concluded that culture is all the work, taste and creativity of humans, namely the entire complex way of life, including knowledge, belief, art, morals, customary law and all other capabilities and habits acquired by humans as a member of society. Cultural indicators are firstly an idea, ideas, values and regulatory norms, secondly as an activity of patterned behavior from humans in a community, thirdly objects made by humans.